Sensitivity analysis of air gap size of non linear inductance in passive mains harmonic reduction circuits - Kübrich, Daniel; et al. (Proceedings of the Power Electronics Specialists Conference 2005,, 2005)
Regulations like IEC 1000-3-2 impose limits on the line input current harmonics. Passive solutions to obtain mains harmonic reduction still dominate the consumer and PC market segment. Typically linear inductors are used in this application. However, some inductors found in practical designs operate in the saturation region even at power levels to be tested for compliance. On the other hand, nearly all publications dealing with design of the passive MHR circuits assume a linear inductor. This paper investigates the usefulness of non linear inductors in passive MHR circuits by extracting the non linearity and modeling the inductor. A given non linear inductor was built in a typical bridge rectifier - electrolytic capacitor configuration. The measurements confirm the compliance with the regulation. A comparison of the measurement with simulations based on the derived model reveals the usefulness of the model. Thus simulations allow for a sensitivity analysis of the air gap size with respect to compliance of the IEC 1000-3-2. This calculation requires a reasonable scaling of the measured inductance for other air gap sizes. The paper describes a suitable scaling method. A MATLAB program simulates the steady state input current wave form of the passive MHR circuit implementing the scaled non linear inductor and verifies whether the regulation is fulfilled or not. The simulations reveal the range of air gap size leading to a valid design. While the linear inductor needs either a larger number of turns in case of a larger air gap or is no longer able to comply with the IEC 1000-3-2 the non linear inductor allows for a certain variation. The sensitivity analysis demonstrates that the non linear inductor allows for some manufacturing tolerance of the air gap if designed accordingly. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.lselek.sensit